2022
DOI: 10.1002/ajmg.c.31993
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne expert physician perspectives on Duchenne newborn screening and early Duchenne care

Abstract: Duchenne muscular dystrophy (DMD) is a progressive, fatal neuromuscular disorder typically diagnosed between 4 and 5 years of age. DMD currently has five FDA approved therapies, which has led to increased interest in newborn screening (NBS) for DMD. Our objective was to explore the perspectives and predicted practices of physicians (primarily neurologists) who will likely be responsible for the follow-up of infants identified with DMD through NBS. A short survey was developed and distributed to physicians who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…The recent addition of spinal muscular atrophy (SMA) to the RUSP in 2018 has set a precedent for neuromuscular disorders to be included in NBS panels. Expert DMD care physicians [ 36 ] and affected families prefer early diagnosis for prompt access to treatments that are most effective in the newborn stage [ 30 ]. Therapies for DMD tend to be more impactful before significant muscle degeneration occurs [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent addition of spinal muscular atrophy (SMA) to the RUSP in 2018 has set a precedent for neuromuscular disorders to be included in NBS panels. Expert DMD care physicians [ 36 ] and affected families prefer early diagnosis for prompt access to treatments that are most effective in the newborn stage [ 30 ]. Therapies for DMD tend to be more impactful before significant muscle degeneration occurs [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with perspectives of HCPs from the United States (US), where substantial advocacy for NBS for DMD has been perceived. 27 , 28 This is perhaps a testament to the stringent pharmaceutical regulatory landscape and health technology assessment processes within Australia, precluding the availability of reimbursed and approved therapeutic interventions for DMD outside of access to oral glucocorticoids. 29 In contrast to caregivers who generally felt empowered by an early diagnosis which they perceived had multiple primary and secondary benefits to the newborn and family, HCPs in our study expressed greater uncertainty about the net benefits of a newborn diagnosis, with notable concerns over the psychosocial harms of diagnostic knowledge through NBS without a recourse to therapeutic intervention early in life.…”
Section: Discussionmentioning
confidence: 99%
“…DMD is medically evaluated in several manners, including via laboratory work, muscle biopsy, gene analysis, electromyography, and cardiac testing ( Venugopal and Pavlakis, 2022 ). The possibility of newborn screening has been extensively discussed, and a recent survey revealed that most DMD physicians would see a benefit in newborn screening and feel that the DMD care community is ready for this ( Armstrong et al, 2022 ). This may be of greatly advantageous, as the majority of DMD physicians also indicated that they would recommend initiating therapies much earlier than the typical age at which DMD is currently diagnosed ( Armstrong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of newborn screening has been extensively discussed, and a recent survey revealed that most DMD physicians would see a benefit in newborn screening and feel that the DMD care community is ready for this ( Armstrong et al, 2022 ). This may be of greatly advantageous, as the majority of DMD physicians also indicated that they would recommend initiating therapies much earlier than the typical age at which DMD is currently diagnosed ( Armstrong et al, 2022 ). However, this has not yet become standard ( Birnkrant et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%